Corticomotor excitability and proprioceptive acuity in chronic lateral epicondylalgia - Dessureault, Liam (University of Ottawa (Canada), 2008)
Chronic lateral epicondylalgia (LE) is a common musculoskeletal condition which has been associated with the presence of distinct local sensorimotor abnormalities. Despite this, little is known about central motor system function and forearm/wrist kinesthetic acuity in cases of chronic LE. The purpose of this pilot study was to determine whether there are adaptive neurophysiological changes occurring at the corticomotor level in individuals presenting with chronic unilateral lateral epicondylalgia, and whether the same individuals present deficits in proprioceptive acuity for weight discrimination and manual dexterity. Methods. For this descriptive, case-controlled study, 14 individuals with chronic LE and 16 age- and gender-matched controls were recruited. LE-related disability was measured with the quickDASH questionnaire and proprioceptive acuity was estimated by way of a weight discrimination task. The Grooved Pegboard Test was used to derive an index of manual dexterity and transcranial magnetic stimulation was used to assess four indices of corticomotor excitability in wrist extensor muscles. Results. Proprioceptive acuity was decreased in the affected arms of LE participants (p=0.001). There were no differences in manual dexterity or indices of corticomotor excitability between arms (p > 0.05) for both groups, but manual dexterity of each the affected and unaffected arms was correlated with resting corticomotor thresholds (p=0.0001 and p=0.04, respectively) a relationship which was not found in the control group. Discussion. Proprioceptive acuity was deteriorated in our sample of chronic LE. Though the clinical significance in this population is unknown, it is hypothesized that such deficits may hamper force perception during functional activities. The relationships existing bilaterally between manual dexterity and motor thresholds suggest that "crossed" modulation of corticomotor excitability may be further influenced by the presence of musculoskeletal dysfunction and/or chronic musculoskeletal pain. While mechanisms responsible for such changes are unclear, these findings merit confirmation in larger patient samples.
Keywords: Health Sciences, Recreation.